GATA6 Exerts Potent Lung Cancer Suppressive Function by Inducing Cell Senescence - Chen, Wensheng; Chen, Zhipeng; Zhang, Miaomiao; Tian, Yahui; Liu, Lu; Lan, Ruirui; Zeng, Guandi; Fu, Xiaolong; Ru, Guoqing; Liu, Wanting; Chen, Liang; Fan, Zhenzhen (Frontiers in Oncology, 2020)
Lung cancer is the leading cause of cancer related deaths worldwide. Tumor suppressor genes (TSGs) play a critical role in restricting tumorigenesis and impact the therapeutic effect of various treatments. However, TSGs remain to be systemically determined in lung cancer. Here we identified GATA6 as a potent lung cancer TSG. GATA6 inhibited lung cancer cell growth in vitro and tumorigenesis in vivo. Mechanistically, GATA6 upregulated p53 and p21 mRNA while inhibited AKT activation to stabilize p21 protein, thus inducing lung cancer cell senescence. Furthermore, we showed that ectopic expression of GATA6 led to dramatic slowdown of growth rate of established lung tumor xenograft in vivo.